Les risques d’atteintes à l’environnement : la situation en France - M., R. (Assurances)

(untitled) (HEC Montréal, 1988)
The author examines certain documents of the GARPOL co-reinsurance group formed in France in 1977 to provide an answer to environmental and pollution claims. This group, which consists of a pool of foreign and French reinsurers, is involved in providing coverage for environmental risks and functions under the aegis of a steering committee whose responsibilities include the administration and definition of guidelines in the event of a claim. The author also provides an overview of the French policy model.